2011
DOI: 10.1111/j.1365-2567.2011.03439.x
|View full text |Cite
|
Sign up to set email alerts
|

Both CD4+ FoxP3+ and CD4+ FoxP3 T cells from patients with B‐cell malignancy express cytolytic markers and kill autologous leukaemic B cells in vitro

Abstract: Summary Cytotoxic CD4+ T cells have been found in patients with chronic lymphocytic leukaemia (CLL) and seem to be involved in the regulation of malignant B cells. The CD4+ T regulatory cells (Tregs) can regulate various immune cells, including B cells, by inducing their apoptosis. Hence, different subgroups of CD4+ T cells may be involved in the regulation of malignant B cells. In this study, the cytotoxic phenotype and function of various CD4+ T‐cell subgroups were investigated in patients with B‐cell malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 57 publications
7
23
0
Order By: Relevance
“…Additionally, Tregs are known to kill B cells through Fas-FasL interaction or through the release of cytolytic molecules (46,47). So, further study is needed to identify mechanisms involved in direct FL B cell inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Tregs are known to kill B cells through Fas-FasL interaction or through the release of cytolytic molecules (46,47). So, further study is needed to identify mechanisms involved in direct FL B cell inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…8). Linqvist et al [46] looked at expression of cytolytic markers and tumour cell killing by CD4 + T cells in CLL patients and demonstrated that CD4 + T cells were capable of cell killing and increased expression of the cytolytic marker CD107a globally on all CD4…”
Section: Foxp3mentioning
confidence: 99%
“…In previous studies, elevated percentages or levels of Treg cells were reported in the total T-cell population isolated from tumor tissues or peripheral blood in a variety of hematological malignancies, including B-cell non-Hodgkin lymphoma (17), Hodgkin lymphoma (18), chronic lymphocytic leukemia (19)(20)(21), multiple myeloma (22) and AML (5)(6)(7)(8). Treg cells accumulating in the peripheral circulation of AML patients mediate vigorous suppression via IL-10 and TGF-β as well as contact-dependent mechanisms (6).…”
Section: Cytokinementioning
confidence: 99%